Tutoring for the development of the assertiveness of elementary school students in Trujillo, Peru - Esteves-Pairazamán, Ambrocio Teodoro (2020)
The study consisted of determining the effectiveness of the tutoring to develop the assertiveness of the primary school students, who initially showed problems of aggression and shyness. The research was conducted in two groups of students, each consisting of 32 students, divided into room "A" (experimental group) and "B" (control group). The research is of an explanatory, quasi-experimental level. The general hypothesis was put forward: tutoring develops the assertiveness of students in the third grade of primary education in educational institutions in the province of Trujillo, Peru; in addition to two specific hypotheses. Pre-tests and post-tests were applied to both groups of students. The results showed greater levels of assertiveness and lower levels of aggressiveness in the students to whom the tutoring program was applied, in relation to the group of students who did not receive it, who did not show great variations. For the hypothesis test, the chi-square test was applied, where all the results obtained were greater than 3.8415, which, for a confidence level of 95% and margin of error of 5%, validate the hypotheses raised by the authors.